Multihost Transmission of Schistosoma mansoni in Senegal, 2015–2018 - Catalano, Stefano; Léger, Elsa; Fall, Cheikh B. (RESEARCH, 2020)
In West Africa, Schistosoma spp. are capable of infecting multiple definitive hosts, a lifecycle feature that may complicate schistosomiasis control. We characterized the evolutionary relationships among multiple Schistosoma mansoni isolates collected from snails (intermediate hosts), humans (definitive hosts), and rodents (definitive hosts) in Senegal. On a local scale, diagnosis of S. mansoni infection ranged 3.8%–44.8% in school-aged children, 1.7%–52.6% in Mastomys huberti mice, and 1.8%– 7.1% in Biomphalaria pfeifferi snails. Our phylogenetic framework confirmed the presence of multiple S. mansoni lineages that could infect both humans and rodents; divergence times of these lineages varied (0.13–0.02 million years ago). We propose that extensive movement of persons across West Africa might have contributed to the establishment of these various multihost S. mansoni clades. High S. mansoni prevalence in rodents at transmission sites frequented by humans further highlights the implications that alternative hosts could have on future public health interventions.
Emerging infectious diseases, 26(6), 1234.
Keywords: Anna Borlase; Samba D. Diop; Duncan Berger; Bonnie L. Webster; Babacar Faye; Nicolas D. Diouf; David Rollinson; Mariama Sène; Khalilou Bâ; Joanne P. Webster; University Cheikh Anta Diop; Senegal; CEA-AGIR